Transcriptomic responses associated with kidney injury and repair in acute decompensated heart failure. (25th November 2020) - Pilbrow, A; Rademaker, M.T; Ellmers, L.J; Palmer, S.C; Davidson, T; Mbikou, P; Scott, N.J; Charles, C.J; Endre, Z.H; Richards, A.M
Abstract: Background: The discovery of new markers for acute kidney injury (AKI) in acute decompensated heart failure (ADHF) has been hampered by an incomplete understanding of the pathological processes underlying AKI in ADHF. Purpose: In a sheep model of ADHF, we investigated changes in kidney gene expression in response to the development of, and recovery from, ADHF. Methods: We collected serial kidney biopsies from 6 sheep prior to rapid cardiac pacing (day 0), after development of ADHF (pacing @220bpm for 14 days), and at the end of a 25-day (non-pacing) recovery period. Serial biopsies were supplemented with kidney samples collected post-mortem from animals undergoing a similar pacing/recovery protocol, giving a total of 11 "baseline" (B), 13 "heart failure" (HF) and 8 "recovery" (R) samples. We prepared RNA-Sequencing libraries using total RNA and Illumina TruSeq stranded mRNA library kits. Hormonal, haemodynamic, biochemical and urine measurements were also performed in all sheep before, during, and after development of ADHF. The study followed the principles of laboratory animal care and was approved by our institution's Animal Ethics Committee. Results: We observed profound changes in hormonal, haemodynamic, biochemical and urine measures of cardio-renal injury in all sheep, confirming simulation of the peripheral consequences of ADHF, including clinically-relevant kidney dysfunction. This occurred in conjunction with altered kidney expression of 982 genes during ADHF development and 1, 807 genes during ADHF recovery (p adj.<0.05, Fig 1). During ADHF development, changes in kidney gene expression were associated with activation of the pro-inflammatory p38 MAPK pathway and repression of several anti-inflammatory and reno-protective pathways, including eNOS signalling (all p adj.<0.001). In contrast, during ADHF recovery, changes in kidney gene expression were associated with reactivation of reno-protective pathways repressed during ADHF development, activation of anti-fibrotic pathways (including PTEN signalling) and repression of pathways that mediate inflammation and renal injury (including NF-kB signalling, all p adj.<0.001). Among 431 ADHF "responsive" genes (i.e. those that increased during ADHF development and decreased during ADHF recovery, or vice versa, Fig. 1), 37 genes encoded proteins detectable in plasma or urine and may represent markers of kidney repair in ADHF. Although most gene expression changes were transient, 192 genes remained altered after 4-weeks recovery (p adj.<0.05, Fig 1). Of these, 13 genes were predicted to encode proteins detectable in plasma or urine and may represent persistent markers of kidney injury in ADHF. Conclusion: Our data provide the first insight into the gene pathways associated with kidney injury and repair in ADHF, in an established ovine model. Understanding the pathological processes underlying AKI in ADHF may enable discovery of novel markers for monitoring kidney injury and repair in ADHF. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Health Research Council of New Zealand, Heart Foundation of New Zealand